2020
DOI: 10.1111/jocs.14983
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for malperfusion syndrome secondary to acute aortic dissection

Abstract: Objective Presenting our experience of treating patients with organ malperfusion secondary to acute aortic dissection. Patients Among 383 patients who underwent aortic repair for acute type A aortic dissection from 1999 to 2017, 107 patients were operated on because of vascular complications. Fourteen patients had coronary, 50 had brain, 3 had paraplegia, 13 had superior mesenteric artery, 21 had lower limb, and 16 had combined organ malperfusion. Age was 65.8 years. Results In coronary malperfusion, three had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The flap prevents the blood flow in the ostium and causes the restriction of the blood flow to the organ. This mechanism we mentioned is responsible for approximately 80% of malperfusion syndromes 4 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The flap prevents the blood flow in the ostium and causes the restriction of the blood flow to the organ. This mechanism we mentioned is responsible for approximately 80% of malperfusion syndromes 4 …”
Section: Discussionmentioning
confidence: 94%
“…This mechanism we mentioned is responsible for approximately 80% of malperfusion syndromes. 4 This neurological deficit may occur due to cerebral embolism of a flap fragment that is detached from its place or from tears and hematomas in the carotids. Therefore, it is vital that the perfusion strategy be fast and effective in acute aortic dissections with carotid involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, 1 report showed the effectiveness of arch vessel stenting after surgical aortic repair for patients with persistent brain malperfusion ( 5 ). Furthermore, peripheral intervention before central aortic repair would prevent severe organ damage, which leads to the improvement of clinical outcomes ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early mortality after open surgery has been reported in 4.1% to 50% of patients. [3][4][5][6][7][8][9][10][11][12][13] The IRAD study demonstrated higher mortality with dissection involving the branches of the aorta.…”
Section: Discussionmentioning
confidence: 99%